Correction: Mapping the interaction sites of Mucin 1 and DNA aptamer by atomic force microscopy. Issue 22 (26th October 2017) - Wang, Nan; Zhang, Miaomiao; Chen, Xuejuan; Ma, Xingxing; Li, Chen; Zhang, Zhe; Tang, Jilin
Abstract : Correction for 'Mapping the interaction sites of Mucin 1 and DNA aptamer by atomic force microscopy' by Nan Wang, et al., Analyst, 2017, 142, 3800–3804.